INDIRECT TEACHER FEEDBACK TO REDUCE STUDENTS’ GRAMMATICAL ERRORS IN WRITING RECOUNT TEXT - Yustin Kustina; R Bunga Febriani; Dedeh Rohayati (JALL (Journal of Applied Linguistics and Literacy), 2020)
Teacher feedback stipulation is a necessity for students especially in the process of writing. It’s become a reflection of their teaching process. The present study, therefore, is aimed at finding out the effectiveness of indirect teacher feedback in reducing students’ grammatical errors in writing recount text, and describing lexico-grammatical aspects of students’ writing that indicate significant progress in error reduction toward indirect teacher feedback as the treatment. The present study implemented a mixed-method with the type of pre-experimental design for the quantitative design and content analysis for the qualitative design. The sample of the present study involved 17 students as the experimental group. Students’ document tests were used to obtain the data. Based on the statistical result, after indirect teacher feedback was implemented on students’ writing recount text especially personal recount text, the t-observed value was higher than t-table value; thereby, the null hypothesis (H0) was rejected and the alternative hypotheses (H1) was accepted. Thus, the use of indirect teacher feedback is effective in reducing students’ grammatical errors in writing personal recount text. In addition, from the analysis content of students’ document tests, verb tense indicated significant progress in error reduction. Based on the findings, it is recommended for English teachers to apply indirect teacher feedback to reduce students’ grammatical errors, especially in teaching writing so that the students' writing can be improved.Keywords: Indirect Teacher Feedback, Recount Text, Students’ Grammatical Errors, Writing